LEFT WING EXTREMIST - A MAJOR SOURCE OF ORGANIZED CRIMES, SMUGGLING AND COMMUNAL VIOLENCE IN THE COUNTRY - Dr.Sumanta Bhattacharya,; Dr. Jayanta Kumar Ray,; Shakti Sinha,; Bhavneet Kaur Sachdev, (Galaxy International Interdisciplinary Research Journal, 2021)
Fearing loss of support the Naxalite oppose any development activities inside the forest areas manipulating them such acts are directed at taking lands, minerals and forest wealth which belong to them. Today Naxalite has ties with different terrorist groups inside and outside the country . External forces support the Naxalite and provide them with weapons and use to weapon violence on big industries and local people to gather fund for themselves . We need to explore and address the socio-economic dimensions of the affected region and find ways to promote development in the region , we need to strengthen local police with better and modernised weapons , communication , technology and satellites to fight against the Left Wing Extremist. We require a multi-pronged strategic to solve the naxal problem .The government both central and state have adopted a holistic approach to tackle this issue .Continues underdevelopment in the region , makes it easier for the Naxalite to misguide and manipulate the innocent population . Today Naxalite have their source in the urban areas also along with we have many LWE supporting institutions gathering the attention of local youths , and even supporter in the media who helps in marketing .